Workplace safety - Ridley, John R.; Channing, John (Butterworth-Heinemann, 1999)
Provides safety advisers with an understanding of basic physics and chemistry, and of the current safety techniques for reducing the risks associated with commonly met industrial processes.
Keywords: Industrial safety.; elektronické knihy; electronic books